2019
DOI: 10.4274/jtgga.galenos.2019.2019.0061
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors, survival outcomes, and surgical practices when dealing with uterine sarcomas: 8 years’ clinical experience

Abstract: Objective:To determine the clinical and pathologic characteristics, prognostic factors, surgical practice, adjuvant therapies, and survival outcomes of patients with uterine sarcoma diagnosed and treated in our institution.Material and Methods:Patients diagnosed and treated for uterine sarcomas at our institution from 2009 to 2017 were retrospectively evaluated. All histologic slides from the specimens underwent a thorough pathologic review by a gynecologic pathologist. The following variables were assessed: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(55 reference statements)
3
7
0
Order By: Relevance
“…This is also consistent with the published literature in which u-LMS was the most frequent subtype of uterine sarcoma [ 2 , 23 ]. The median age in our study group was 49 (40–55.5 years), which is also similar to the previously published studies [ 23 – 25 ]. Previous studies on uterine sarcomas have included carcinosarcoma patients; in some, an almost equal number of carcinosarcoma and u-LMS patients were included in their analysis [ 23 – 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is also consistent with the published literature in which u-LMS was the most frequent subtype of uterine sarcoma [ 2 , 23 ]. The median age in our study group was 49 (40–55.5 years), which is also similar to the previously published studies [ 23 – 25 ]. Previous studies on uterine sarcomas have included carcinosarcoma patients; in some, an almost equal number of carcinosarcoma and u-LMS patients were included in their analysis [ 23 – 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, our study did not include carcinosarcoma patients due to their epithelial origin and because they are no longer considered in the uterine sarcoma group [ 3 ]. This has provided a more relevant analysis of disease characteristics and outcomes knowing of the changes in the classification [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prognostic factors have been recognized from retrospective data to guide therapeutic decisions for uterine sarcoma patients. Patients with old age, advanced stage, high tumor grade, and high mitotic index have been found to have worse prognosis [ 13 , 14 , 15 , 16 ]. However, diagnosis and treatment of uterine sarcoma remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Even with stage I, 11 of 15 patients who relapsed had a high NLR. Previous studies have also reported that high proportions (66.4% and 71.9%) of patients with uterine sarcoma have stage I [ 12 , 15 ]. Treatment options (observation or systemic therapy) for stage I uterine sarcoma including LMS and high grade ESS after surgical resection are controversial and vague according to National Comprehensive Cancer Network (NCCN) guidelines.…”
Section: Discussionmentioning
confidence: 99%